Extracted Electronic Parameters of a Novel Ag/SnO2:In/Si/Au Schottky Diode for Solar Cell Application - Mostefa Benhaliliba (Журнал нано- та електронної фізики)
The effect of indium on the characteristics of Ag / SnO2 : In / Si / Au Schottky diode (SD) is studied. The electronic parameters, ideal factor, the effective barrier, flat band barrier height, the series resistance, the saturation current density of the diodes were extracted from the current voltage (I-V) and capacitance voltage (C-V) characteristics. The series resistance (Rs) determined by Cheung method increases (508-534 Ω) with In doping level while the barrier height still constant around 0.57 V. Norde approximation gives a similar barrier height values of 0.69 V but the series resistance reaches higher values of 5500 Ω.